Developing Mahakarya Vokasi Virtual Reality Game: Player-Centered Design (PCD) with UEQ-Based Analysis - Rezky Anju Picent Marpaung; Amirul, Amirul Mu'minin (Journal of Games, Game Art, and Gamification, 2025)
This research describes the process of doing vocational work in a Virtual Reality (VR) adventure game called VR Mahakarya Vokasi. The game is designed to provide an interactive experience that allows players to engage directly in a virtual adventure using VR technology. The development process involves the design, implementation, and evaluation stages, focusing on vocational product content. This research is based on Player-Centric Design, which places the player at the center of attention. The User Experience Questionnaire (UEQ) method was used to assess the quality of user experience and can help identify issues related to game usage while providing valuable feedback for game development. User experience analysis of 20 respondents at the Vokasi Fest x Festival Kampus Merdeka event at Ismail Marzuki Park, Jakarta, on December 12-13, 2023. This research shows that the VR adventure game is considered “Worthy” of use, which aligns with the UEQ benchmark. Specific aspects include Attractiveness (Excellent), Stimulation (Good), Novelty (Above Average), Efficiency (Above Average), Dependability (Below Average), and Perspicuity (Below Average). Overall, this game, VR Adventure Mahakarya Vokasi, developed as a vocational work, is considered worthy of use.